The impact of trans fatty acids on ADHD in relation to the gut microbiome - He, Nianyang; Zhong, Jiayi; Deng, Songlin; Liang, Jiyu; Li, Qingqing; Chen, Ke (Frontiers in Nutrition, 2025)
Attention deficit hyperactivity disorder (ADHD) is a neurodevelopmental disorder (NPDs) caused by the interaction of genetic and environmental factors. Trans-fatty acids (TFAs), mainly from chemically hydrogenated vegetable oils, are an environmental factor with increased exposure risk in modern diets. Recent studies suggest that TFAs may contribute to ADHD development through two pathways: inducing neurodevelopmental damage and indirectly affecting neural function by altering gut microbiota, though specific mechanisms remain unclear. This review focuses on two critical neurodevelopmental phases (perinatal period and adolescence) to explore the relationship between TFA exposure and ADHD, and to investigate the pathways through which TFAs affect ADHD by disrupting gut microbiota homeostasis. Although the association between TFA exposure during adolescence and ADHD is controversial, the harm of perinatal TFA exposure is undisputed. Shared neurodevelopmental damage mechanisms across both stages support reducing TFA intake during critical neurodevelopment. TFAs also impair neurodevelopment and brain function through the microbiota-gut-brain axis (MGBA) by disrupting gut microbiota homeostasis and activating neural, immune, and endocrine pathways. Thus, based on the harmful effects of TFAs during critical periods and the functional network by which TFAs contribute to ADHD pathogenesis through gut microbiota, this review supports dietary TFAs restriction as an ADHD prevention strategy.